Upshot of virulence markers and effects of temperature and pH on haemolytic bacteria in South-west Nigeria - Olubukola Olusola-Makinde; Michael Bayode; Ayomikun Somefun (Microbes and Infectious Diseases, 2022)
Background: Virulence is the extent of pathogenicity displayed by majority of pathogens and yardstick that efficiently distinguishes pathogenic and non-pathogenic organisms.Effects of pH, temperature and incubation period were studied on capsule-positive bacteria isolated from Onyearugbulem stream, Akure. Methods: Water samples from Onyearugbulem stream in Akure was collected in sterile 500ml sample bottles. Water samples obtained from the stream were subjected to microbiological analysis. Implicated bacteria were tested for haemolysis and virulence determination via blood agar (5% v/v) and for the presence of capsule using India ink. ß-haemolytic bacteria were subjected to different temperature (15 °C – 60 °C) and pH (6.0 – 9.0) ranges. pH conditions were achieved by the addition of 0.01M NaOH and 0.01M HCl to media  before sterilization. The zones of clearance (mm) were measured at 24 h, 48 h and 72 h. Results: Proteus penneri showed the highest haemolytic activity (56 mm) at 28 °Cafter a duration of 72 h. Bacillus cereus showed the highest haemolytic activity (52 mm) at pH 8.5, after 72 h Dye degradation was optimum at 10 to 12 h at 37 °C which showed the haemolytic bacterial organisms were capsule-positive. Conclusion: The findings in this study revealed that bacteria present in Onyearugbulem stream contained virulent factors with highest activity at ambient temperature (28 °C) which indicate the poor quality of the stream and thereby constitute serious health threat to man and animals